New variants of AvrPiz-t identified in Pyricularia oryzae from Malaysia - Freddy Yeo, Kuok San; Elissa stella, Rafael; Ewe, Zhang Hua; Ang, Poh Sim; Nor Ain, Hussin; Tu Anh, Vu Thanh; Chung, Hung Hui; Lai, Lee San; Ting, Hieng Ming; Yongmei, Bao (Elsevier B.V., 2024)
Rice blast disease (causal agent: Pyricularia oryzae) is an important rice disease worldwide as it can cause significant yield loss. Resistance genes in rice can recognise the corresponding avirulence genes (Avr-gene) of P. oryzae and suppress the attack of the pathogen as proposed in ‘gene-for-gene’ interaction. This interaction is highly specific. The resistance will be rapidly breakdown owing to the plasticity of Avr-gene. The breaking down of disease resistance can cause problem in managing the disease as well as sustaining a resistant rice variety. This paper aimed to study and analyse the sequence variation of AvrPiz-t gene from P. oryzae isolates in Malaysia (Sarawak) together with AvrPiz-t sequences available from National Centre for Biotechnology Information (NCBI). This study compared the AvrPiz-t haplotype found with previously reported haplotypes. A total of 20 Malaysian P. oryzae isolates were obtained from six divisions of Sarawak and were verified using internal transcribed spacer. Together with seven Malaysian P. oryzae isolates from a previous study, a total of 27 AvrPiz-t gene sequences from Malaysian isolates were successfully amplified and verified. The AvrPiz-t open reading frame (ORF) of 27 Malaysian isolates were aligned with 123 AvrPiz-t ORF from other countries that were available in NCBI database and 100 AvrPiz-t ORF from a previous study (Total = 250 sequences). Unique sequences were identified and translated into amino sequence. The amino acid sequences were aligned with haplotype sequences from previous studies. In total, there were 19 AvrPiz-t haplotypes, with eight newly identified haplotypes. The AvrPiz-t haplotypes were distributed across 14 countries with haplotype H9 as the dominant haplotype. Neutrality tests were performed for the 250 AvrPiz-t ORF sequences. The 250 isolates of P. oryzae were undergoing directional natural selection.. Detached leaf inoculation using filter paper method of selected Malaysia (Sarawak) P. oryzae isolates carrying one of the new AvrPiz-t haplotypes showed different level of pathogenicity towards Sarawak rice landraces. The data obtained serves as baseline information for disease management in Malaysia, especially for Sarawak state. Additionally, the information is also a reference for future rice breeding program in Sarawak.